KEBIJAKAN TIONGKOK DALAM MENGATASI HUMAN TRAFFICKING STUDI KASUS: MAIL ORDER BRIDE TAHUN 2015-2019 - Julianis "; Umi Oktyari Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The One Child Policy, which was enforced from 1979 to 2015, was aimed at controlling China's population and economic growth. The one child policy in China has caused an imbalance in the male and female population where the number of males exceeds around 25%. Considering that marriage is an important thing in Chinese culture, the shortage of women is resolved by mail order brides which cause many problems, especially the occurrence of human trafficking. This paper discusses the strategies used to overcome these problems and the results. This study uses qualitative methods, with data collection techniques through document analysis sourced from several books, journals, final assignments, documents and websites. This study uses the perspective of Constructivism and International Cooperation Theory. The results of the study show China's success in carrying out several collaborations, namely multilateral cooperation with the United Nations, bilateral cooperation with Indonesia and Vietnam, as well as cooperation with regional organizations in its region, namely COMMIT. This success can be seen in the UNHR (United Nations Human Rights) Universal Periodic Review of China in 2019. Keyword : Mail Order Bride, International Cooperation, Policy